Long‐term fertilization effects on soil organic carbon stocks in the irrigated desert soil of NW China. Issue 4 (15th May 2015) - Chai, Yanjun; Ma, Shiming; Zeng, Xibai; E, Shengzhe; Che, Zongxian; Li, Lianfang; Duan, Ran; Su, Shiming
Abstract Soil samples from the Hexi Corridor located at the arid regions of NW China were collected from a 23‐y‐old field experiment. Effects of fertilization on soil organic C (SOC) fractions and the distribution of added OC in the different SOC fractions were studied. The results showed that the long‐term applications of sole organic manures or in combination with inorganic N fertilizer significantly (P < 0.05) increased the OC stocks in the particulate organic matter (POM), light fraction organic matter (LFOM), and heavy fraction organic matter (HFOM) by 24.8–159.6%, 55.2–224.4%, and 6.2–57.8%, respectively, compared to the non‐fertilized treatment (CK). The average OC stock in the HFOM was higher than those of the POM and LFOM, and the conversion rate of the added OC to the OC stock of the HFOM was also higher than those of the POM and the LFOM, showing that SOC was mainly sequestrated in the HFOM. The increase of OC stock in the HFOM resulted in the increase of OC stocks in the loosely bound humus, stably bound humus, and tightly bound humus. The OC stocks in the loosely, stably, and tightly bound humus accounted averagely for 16, 19, and 65% of the OC stock in the HFOM. Furthermore, the conversion rates of the added OC to the OC stocks of loosely, stably and tightly bound humus were 2.3%, 1.5%, and 5.5%, respectively. Additionally, a significant (P < 0.01) positive linear correlation was found between the annually added OC amounts and the C sequestration rate. These results indicated that tightly bound humus was the most important component for OC sequestration in the irrigated desert soils of the Hexi Corridor and that SOC is not saturated in this region.